Influence of Gender on Satisfaction of Library School Students with SIWES in Tai Solarin University of Education - Simisaye, Ahmed O.; Awodoyin, Anuoluwa F.; Osisanwo, Temitope O. (MiddleBelt Journal of Library and Information Science, 2020)
Students’ Industrial Work Experience Scheme (SIWES) is critical in the training of undergraduates in Library and Information Science (LIS) Programs in Library Schools worldwide. Students’ satisfaction is an important means of assessing the training including SIWES. Understanding students’ perceptions and satisfaction is important in efforts to enrich the students’ learning experiences. Gender difference has also become significant in teaching and learning. Many studies have been carried on SIWES and satisfaction, but it is observed that in the context of Nigeria, significant studies have not probe the impact of gender on satisfaction of SIWES. This study therefore investigated the influence of gender on level of satisfaction of LIS Undergraduates of Tai Solarin University of Education (TASUED), Ijagun, Ogun State. Descriptive survey design was adopted using total enumeration technique to collect data from all 130 LIS undergraduates of TASUED using the questionnaire. One hundred and twenty copies of the questionnaire were returned and used for the analysis. The study found out that the level of satisfaction of the undergraduates was moderate as the overall mean is 1.78 and there is significant difference in the level of satisfaction of undergraduates based on gender as (t=0.55; P<0.05). The study recommended that stakeholders should be considering the satisfaction of the students and the impact gender plays in the level of satisfaction of the students when planning and implementing SIWES programmes.